Convolutional Neural Network Technology and Deep Learning for X-ray Image-Based Pneumonia Identification - E. Thenmozhi; Bharath R. K.; Gokulselvam R; Anbarasu K (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Pneumatic systems, which transfer power through compressed air or gas, are used in pneumatic detection to identify certain events or situations. Pneumatic detection systems can benefit from the integration of deep learning, a kind of artificial intelligence, to increase their capabilities in a number of ways. Pneumatic data may be used to train deep learning algorithms to identify patterns. Through the examination of these departures from typical behaviour, anomalies that point to malfunctions or irregularities in pneumatic systems may be identified. Pneumatic data from the past may be used by deep learning algorithms to understand when parts are likely to break. This makes preventative maintenance possible, which lowers downtime and keeps expensive malfunctions at bay. By evaluating sensor data in real-time, deep learning algorithms are able to identify the underlying causes of pneumatic system malfunctions. This can enhance system performance and dependability by assisting professionals in promptly identifying and resolving problems. Pneumatic system characteristics may be optimised using deep learning approaches to increase effectiveness and performance. They are able to instantly adjust system settings to changing operating circumstances by evaluating data from several sensors. Pneumatic data may be analysed by deep learning models to guarantee product quality throughout production operations. They enable early intervention to uphold product standards by detecting flaws or variations from specifications. Huge X-ray image collections are gathered and classified as either normal or pneumonia-infected. To improve the variability of the training set, preprocessing operations may include augmentation methods, normalisation, and picture shrinking to a uniform size. Because CNNs can automatically extract hierarchical characteristics from pictures, they are commonly employed. Variants of VGG, ResNet, Inception, and AlexNet are examples of common designs. These architectures are frequently adjusted or changed to meet the particular needs of the job. Using supervised learning, the CNN model is trained on the labelled dataset. By modifying its parameters to minimise a loss function, usually cross-entropy loss, the model learns to map input X-ray pictures to their corresponding classes (normal or pneumonia-infected) during training.